Three new species and new records of Stenichnodes Franz (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
Three new species of Stenichnodes Franz are described, all placed in the nominotypical subgenus, and occurring in Ivory Coast: S. cordicollis sp. n., S. spinosus sp. n., and S. bouakensis sp. n. Stenichnodes (s. str.) error Jałoszyński is recorded from a second locality in Kenya, and S. (Parastenichnaphes) ceylonensis (Franz), previously known to occur in Sri Lanka, is recorded from Tamil Nadu, India. Two of the newly described species are unusual in having the aedeagi with parameres; diagnostic value of this character, and the presence or absence of metaventral carinae, are discussed.